Home Security System Using Zigbee - Norlezah, Hashim; Mohd Amir Hafifi, Abdul Razak; Fakrulradzi , Idris (Penerbit UTM Press, 2015)
This paper explains the design and implementation of home security systems using the most widely deployed enhancement to the 802.15.4 standard, which is better known as Zigbee. Home security systems nowadays are expensive and complicated to install. Two types of sensors were used in this project, motion sensor and magnetic door sensor. These sensors were used as the end device to detect any intruder. If any intruder bypasses the motion sensor or the magnetic door sensor, a signal will be sent to the system and the alarm will be triggered together with Graphical User Interface (GUI) display on a personal computer. The performance of the designed system was analyzed in terms of detectable range and delay. Result shows that the designed system is capable of detecting up to 22 meters of distance for indoor use at maximum delays of 15 seconds. The home security system using Zigbee has been successfully designed, implemented and analyzed.